Pemilihan Sumber Pendanaan Perusahaan Berdasarkan Hipotesis Pecking Order - Ida . (Universitas Kristen Maranatha, 2010)
This Article proposes a rational justification to the Pecking order Hypothesis through relationship with Modigliani Miller Proposition I. The reason to support our justification is 7 (seven) incentives of Pecking order Hypothesis. The 7 (seven) incentives of Pecking order Hypothesis are tax incentive for debt, the bankruptcy costs mitigation incentive, signalling incentive due to information asymmetry, under/ over – investment mitigation incentive due to information asymmetry, asset substitution incentive, managerial risk aversion incentive, and transaction costs incentive. The implications are 5(five) incentives to prefer use debt than equity and 2 (two) Incentives to prefer use equity than debt. Keywords: Incentives of Pecking order Hypothesis, Modigliani Miller Proposition I.